LEARNING MANAGEMENT IN PANCASILA AND CITIZENSHIP EDUCATION FOR SHAPING STUDENTS’ DISCIPLINE: A QUALITATIVE STUDY AT AN INDONESIAN ISLAMIC JUNIOR HIGH SCHOOL: - - Nur Hidayah; Jamil Jamil; Aloysius Hardoko; Marwiah Marwiah (SOSIOEDUKASI, 2025)
This study aims to describe learning management in the subject of Pancasila and Citizenship Education (PPKn) in shaping the discipline of grade VII students at MTs Negeri Samarinda. The research uses a qualitative approach with a descriptive method. The research subjects consisted of one PPKn teacher and four students of grade VII who were selected through purposive sampling techniques based on variations in the level of discipline of different students. Data was obtained through in-depth observation and interviews to explore the implementation of learning management and students' responses to the application of discipline in the classroom. The results of the study showed that PPKn teachers manage learning through structured planning, organization, direction, and supervision, so as to be able to foster student discipline in four main aspects: neatness of dress, punctuality, task completion, and behavior during learning activities. Students in general have shown a good, disciplined attitude, although there are still some obstacles such as differences in learning styles and limited learning time. Overall, the learning management implemented by teachers plays an important role in shaping the culture of discipline in madrasas, and needs to be supported by habituation and continuous strengthening.